An ethnographic approach to understanding preferences for water supply and treatment in rural India - Linneck, Sandra (Cranfield University, 2016)
Increasing water scarcity and contamination pose a danger to the health of a considerable number of the world’s population. Decisions regarding water supply and treatment are usually made in a top-down fashion. The end-users, however, still react to these decisions and the provided water facilities and treatment options. These reactions include the rejection of certain water supplies or treatment options and own provisions for a supply with safe and sufficient drinking water. This study investigates the socio-cultural and economic factors which influence the rural Indian population’s preferences regarding their water supply and treatment. The study has been carried out, employing an ethnographic approach to the field, in two villages in Karnataka, in South India, conducting 18 in depth, problem-centred interviews, participant observation, and two group discussions. The key findings show a ubiquitous lack of education regarding water and related hygiene-measures, water policies and water contamination. This led to uninformed opinions about water supplies and treatment. Socio- cultural factors, along with pragmatic factors such as reliability of water supply and treatment, along with the physical ease of use regarding their operation, were found to be more important for the villagers’ preferences than economic factors. Most households viewed piped water supply as an unreliable source of water, also in terms of water quality. The households and NGO interviewees favoured individual community-based solutions on village level, whereas the political decision-makers were in favour of centralised solutions, usually through piped supply. These findings show a need for long-term, in-depth studies of individual socio-cultural factors and the importance of decentralised and individually fitted water supply and treatment solutions. The fact that perceptions of water supplies and treatment, based on similar concepts could be found in two villages, in entirely differing regions in South India, suggests the significance of these findings beyond Karnataka and the Indian borders.
Keywords: Water supply; participant observation; community-based approach; religious beliefs; water